Onycholysis in an elderly woman: Proposal for treatment with Coix seed extract administration - Horiuchi, Yasuhiro (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: The exact etiology of onycholysis, which is characterized by the painless separation of the nail from the nail bed, remains unclear. Currently, there are no established effective treatments for this condition. Coix seed extract (C-S extract), a traditional Chinese medicine, is recognized for its various biological properties. Case Illustration: This report describes a case of onycholysis affecting the left index finger of a 62-year-old female patient, with initial symptoms appearing three months prior. Despite ongoing internal administration of C-S extract, the patient experienced a recurrence of onycholysis on both the index finger and pinky finger of the left hand a few months later. Notably, both the initial occurrence and the relapse were resolved with the use of oral C-S extract. Discussion: C-S extract is commonly utilized in both medicinal and cosmetic application; however, its underlying biological mechanism remain largely unexplored. It has been suggested that the extract may serve as an effective anti-aging agent for the skin. Nonetheless, it is perceived that the potency of C-S extract is relatively limited. Conclusion: Therefore, further scientific evaluation of the biological function of C-S extract is warranted. While it shows promise as an anti-aging agent and has a favorable safety profile, its overall efficacy appears to be moderate.